Sitting intention in open spaces using the theory of reasoned action - Atefeh Movahedfard, 1984-; Hasanuddin Lamit, supervisor; Fakulti Alam Bina (2012)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2012